Analisis Variabel-variabel Penguat Kewirausahaan Sosial untuk Pengentasan Kemiskinan Keluarga - Hamdan Yuafi; Faqih Nabhan (Universitas Batanghari Jambi, 2023)
This research was conducted based on a big question of what kind of social entrepreneurship could increase the condition of familiy to alleviate poverty. In this study, we take four variables that can improve the relationship of social entrepreneurship and family poverty alleviation, these are Zakat Infaq Shodaqoh (ZIS) for business purposes, financial literacy, social facilitation and frugal social innovation. The last variable is a new variable that has never existed before. Researchers synthesized these variables from two different variables, namely Social Innovation and Frugal Innovation.The method used in this study is Mixed Research with an Explanatory Sequential Design approach, which combines quantitative data analysis and then confirmed the results through in-depth interviews. This study took a sample of 195 Beneficiary Families (KPM) of the Program Keluarga Harapan (PKH) in Semarang Regency. One of the results taken into account in this study is that social entrepreneurship coupled with good financial knowledge can increase the condition of familiy to alleviate poverty optimally or significantly. Meanwhile, from the partial analysis, it is shown that the variables of social entrepreneurship, financial literacy and frugal social innovation and social assistanceship have a positive and significant effect on poverty alleviation.